Histopatologi Ikan Kerapu Macan yang Diimbuhi Bakteri Asam Laktat dan Diuji Tantang Vibrio alginolyticus (HISTOPHATOLOGY OF TIGER GROUPER SUPPLEMENTED WITH LACTIC ACID BACTERIA AND CHALLENGED BY VIBRIO ALGINOLYTICUS) - ., Nursyirwani; Asmara, Widya; Wahyuni, Agnesia Endang Tri Hastuti; ., Triyanto (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
Supplementation of lactic acid bacteria (LAB) as probiotic in aquaculture has been reported toincrease fish growth and enhance their resistance against diseases. The aim of this study was to figureout histological changes of tiger grouper (Epinephelus fuscoguttatus) fed with LAB isolates followed bycha